Pengaruh Penggunaan Modul Elektronik Interaktif Berbasis Canva pada Materi Kerja Sama Ekonomi Internasional Terhadap Minat Belajar Siswa Kelas XI MAN 1 Medan - Dayinati, Erli; Siar Meiriza, Mica (SJEE (Scientific Journals of Economic Education), 2025)
This study aims to analyze the impact of Canva-based interactive electronic modules on students' learning interest in the topic of International Economic Cooperation. This study adopted a quantitative experimental design with a one-group pretest-posttest method. The research sample consisted of 30 students of grade XI MAN 1 Medan, selected through a purposive sampling technique. A learning interest questionnaire was used as the research instrument, administered before and after the intervention. The results of the statistical analysis showed an increase in the average score from 36.70 in the pretest to 41.63 in the posttest. The normality test confirmed the normal distribution of the data, while the paired sample t-test obtained a significance value <0.000 (p <0.05). This indicates a significant effect of Canva's interactive module on increasing students' learning interest. Therefore, the use of Canva-based learning media has been proven effective in fostering students' learning interest.